Enhancing Vocabulary Mastery Using Audiovisual Learning Wordwall - Jayanti, Tri; Rosdiana, Alivia (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
This study examined Enhancing Vocabulary Mastery Using Audiovisual Learning Wordwall among fourth-grade elementary school students. Elementary schools faced challenges with limited instructional time for English language learning, creating a need for more efficient and engaging vocabulary teaching methods. This research used a pre-experimental design with one group taking both a pretest and posttest, including 33 fourth-grade students at SDN 1 Purwogondo. The intervention utilized Wordwall interactive audiovisual activities to teach vocabulary related to the